Russian Oil Companies in an Evolving World: The Challenge of Change - Indra Overland (Edward Elgar Publishing, 2020)
This book examines Russia's capacity to respond to a changing world through the lens of the country's oil industry. Against a backdrop of social, political and climatic change, Indra Overland and Nina Poussenkova present a systematic analysis of how modern energy developments in the form of shale oil, offshore oil and the global energy transition are handled.